The Health Status of Lebanese Community Pharmacists: Prevalence of Poor Lifestyle Behaviors and Chronic Conditions - Samer Barake; Rayan Tofaha; Deema Rahme; Nathalie Lahoud (Elsevier, 2021)
Background: Community pharmacists are drug therapy experts providing pharmaceutical care for various patients. Their stressful daily tasks can affect their lifestyle and wellbeing. Objectives: To assess the health status of the Lebanese community pharmacists, to determine the prevalence of chronic conditions and unhealthy lifestyle behaviors, and their association with pharmacists' professional responsibilities. Methods: A cross-sectional study was conducted on 300 randomly selected pharmacists between May and August 2017. A four-page questionnaire was carried out targeting their health characteristics, lifestyle factors, and job details. Results: Thirty-seven percent of the studied sample were males, with a mean age of 30.9 ± 9.1 years and mean Body Mass Index (BMI) of 23.4 ± 3.71 kg/m2. Twenty-six percent were smokers and smoking was significantly related to gender, BMI, workplace region, work shifts, educational level, number of patients/day, and transportation time to work (p < 0.05 for all). Twenty-one percent were alcohol consumers, 89.3% were caffeine consumers, and 41.7% were physically active. Moreover, 72% were fast food consumers, 89.7% consumed sweets, and 87.7% consumed salted food. Concerning chronic diseases, 6.3% were hypertensive and hypertension was significantly related to age, marital status, education level, working hours per day, working days per week, owning a pharmacy, work shift, and the number of patients per day (p < 0.05 for all). Conclusion: Lebanese pharmacists might have a lower prevalence of chronic diseases compared to the general population. However, the prevalence of bad lifestyle behaviors such as low physical activity, smoking, consumption of salt, sweet, fast food, and caffeine is considered high among the study sample and this would raise a concern about pharmacists' awareness and role as healthcare providers.